Service level And Logistic Performance: An Implementation Of Sustainable Quality Assessment - Annas, Mohammad; Humairoh, Humairoh (International Journal of Science, Technology & Management, 2023)
The study aimed to uncover the impact of quality assessment with the instruments of ISO 9001at major hub of logistics companies in Indonesia which divided into three major regions, western region, middle region and northern region of Indonesia. The implementation of ISO used three different variables as components and parameters of assessment which consist of continuous improvement, satisfaction of users and prevention of nonconformities. The methods were used by interviewing and deployment of structured questionnaires to related parties which directly engaged on quality assessment process in daily assignments. The result showed that the implementation of quality instruments such ISO 9001 affecting significantly the quality delivered to users and customers as well as the performance of overall operation held by the logistics companies. The result also showed that the quality of service was not only could be undertaken by two variables but also could be done with more variables that have not been explored. The opportunity of improvement had been implemented by logistics companies through giving optimum services to users and customers.